2020
DOI: 10.21203/rs.3.rs-17943/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic review and meta-analysis of diagnostic delay in axial spondyloarthritis

Abstract: Background . Delay to diagnosis in axial spondyloarthritis (axSpA) is longer than many other rheumatic diseases. Prolonged delay has been shown to associate with poorer outcomes including functional impairment and quality of life. Our aims were to describe 1) global variation in delay to diagnosis, 2) factors associated with delay, and 3) differences in diagnostic delay between axSpA and psoriatic arthritis (PsA).Methods . We searched Medline, PubMed, EMBASE and Web of Science using a predefined protocol in ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Pre‐diagnosis interval has been referred to as diagnostic delay, (time) interval or lag time between symptom onset and diagnosis in published studies 9‐14,16,20,42,43 . We did not use the term “delay” because, according to the systematic review by Scott et al, “delay” is not only value‐laden but also inaccurate as many patients do seek medical attention promptly after symptom onset 41 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre‐diagnosis interval has been referred to as diagnostic delay, (time) interval or lag time between symptom onset and diagnosis in published studies 9‐14,16,20,42,43 . We did not use the term “delay” because, according to the systematic review by Scott et al, “delay” is not only value‐laden but also inaccurate as many patients do seek medical attention promptly after symptom onset 41 .…”
Section: Methodsmentioning
confidence: 99%
“…Early diagnosis and treatment in autoimmune rheumatic diseases (ARDs) have been shown to significantly improve clinical outcomes such as higher rates of response and remission and less radiographic progression as well as patient‐reported outcomes such as better health‐related quality of life and lower productivity loss 1‐8 . However, recent studies suggest that prolonged interval from symptom onset to diagnosis and treatment remains an unsolved problem in patients with ARDs worldwide 9‐15 . For example, in patients with rheumatoid arthritis (RA) where this interval is reported to be relatively shorter compared to other ARDs, a systematic review found that the reported interval remained consistently long over the past 2 decades (4 to 24 months) 13 .…”
Section: Introductionmentioning
confidence: 99%